Psychiatric symptoms and recent overdose among people who use heroin or other opioids: Results from a secondary analysis of an intervention study. (December 2019) - Fendrich, Michael; Becker, Jessica; Hernandez-Meier, Jennifer
Abstract: Background: Drug overdose (OD) is the leading cause of accidental death in the United States and most of these deaths involve opioids. Despite research linking opioid abuse to mental illness, and evidence suggesting a large portion of opioid OD deaths are suicides, OD prevention strategies scarcely take into account mental health risk factors. Methods: We examined a sample of heroin or other opioid users enrolled in an intervention study to determine the prevalence of overdose, the prevalence of suicide attempts in overdose, and whether those with higher levels of psychiatric symptomatology would be more likely to experience a recent OD compared to other opioid users. By performing bivariate analyses and multivariate logistic regression models that controlled for poly drug use, criminal justice status, age, race, gender, and education, we evaluated the association of severe depression, severe anxiety, posttraumatic stress disorder (PTSD) and, psychosis and past three-month OD. Results: Just over 12% (45/368) of recent opioid users reported a recent overdose. Four of these recent overdose victims reported that the overdose was a suicide attempt. Multiple logistic regression analysis revealed that severe depression (odds ratio 2.46; 95% CI: 1.24, 4.89), PTSD (odds ratio: 2.77; 95% CI: 1.37–5.60) and psychosis (odds ratio 2.39; 95% CI: 1.10–5.15) were significantly associated with elevated odds for OD. Conclusions: Findings suggest systematic mental health symptom screening and connection to mental health treatment for opioid users—especially those identified with OD—may be critical for OD prevention. Highlights: A sample of recent opioid users in an intervention study was examined Over 10% of the study sample of recent opioid users reported a recent overdose Almost 9% of recent overdose victims reported that the overdose was a suicide attempt Depressive symptoms, PTSD, and psychosis were associated with recent overdose OD risk assessment tools should include validated mental health screening